The Ecological Competence of Pupils: the Content, Structure and Features of Formation - D S Yermakov (Peoples' Friendship University of Russia (RUDN University), 2008)
The essence of the ecological competence and ecological awareness, their interrelation in the system of categories of environmental psychology and pedagogics have been analyzed. The structure and the content of the ecological competence at the level of general secondary education are submitted.